Annual Plan 1971-72 Government of Manipur - Planning Commission (Planning Commission, 1971)
The Union Territory of Manipur is bounded on the north by the State of Nagaland, on the south by the Lushai Hills, on the cast by the Upper Burma and on the west by the District Cachar in Assam. It has an area of 8628 sq. miles (22,347.2 sq. kilometers): 9/10th of which consists of hills. the oval shaped valley of Manipur consisting of about 1,120 sq. kilometers is situated in the middle surrounded by the hills on all sides. Out of about 854.4 kms. which constitute the boundary line, the approximate length of 352 kms. forms the international boundary line with Burma.
Government of Manipur